Analysis And Improvement Of Drug Supply Chain Risk Management Using House Of Risk (HOR) And Analytical Hierarchy Process (AHP) Approaches - Ernaning Widiaswanti; Heri Awalul Ilhamsah; Rahmad Faizal (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Risk management is required because there is always a chance that problems will develop in supply chain activities. In industries engaged in health services, such as PT. Rukun Putera Bersama, in supply chain activities for the procurement of drugs, there is an opportunity for risks to arise. Therefore, it is necessary to carry out a risk analysis and design mitigation actions to mitigate the risks that are likely to arise in the drug procurement supply chain. This research was conducted using the House of Risk (HOR) model and the Analytical Hierarchy Process (AHP). After conducting the research, it was found that there were 23 risk events and 15 risk agents. There are 10 risk mitigation actions in the drug procurement supply chain. Furthermore, from the 10 mitigation actions, it is reprocessed using AHP. The results of AHP weighting obtained the best alternative strategy, namely the use of digital pharmacy management information system software to regulate and monitor pharmacy management performance.